The Cu–Sn multilevel gradient heterogeneous interface interpenetrative growth mechanism and its regulation strategies - Yulu Ouyang; Yahui Liu; Guoshang Zhang; Tao Huang; Weiwei Lu; Dong Liu; Aikui Liu; Kexing Song (Journal of Materials Research and Technology)
This study investigates the microstructural characteristics of the heterogeneous interface of hot-dip Sn-plated Cu subjected to multistage heat treatment. The findings reveal that, under thermal stress, the phases at the heterogeneous interface exhibit competitive growth. As the diffusion energy of Cu atoms diminishes, the interface undergoes self-stabilization, gradually evolving toward a more stable configuration.